Sensors Proceedings of the Second National Conference on Sensors, Rome 19-21 February, 2014 - Compagnone, Dario; Baldini, Francesco; Di Natale, Corrado; Betta, Giovanni; Siciliano, Pietro; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2015)
This book contains a selection of papers presented at the Second National Conference on Sensors held in Rome 19-21 February 2014. The conference highlighted state-of-the-art results from both theoretical and applied research in the field of sensors and related technologies. This book presents material in an interdisciplinary approach, covering many aspects of the disciplines related to sensors, including physics, chemistry, materials science, biology and applications. ·         Provides a selection of the best papers from the Second Italian National Conference on Sensors; ·         Covers a broad range of topics relating to sensors and microsystems, including physics, chemistry, materials science, biology and applications; ·         Offers interdisciplinary coverage, aimed at defining a common ground for sensors beyond the specific differences among the different particular implementation of sensors.
Proteotronics: Electronic Devices Base on Proteins -- Study of the Role of Particle-Particle Dipole Interaction In Dielectrophoretic Devices for BioMarkers -- Portable, Mulitispot, Label-Free Immunoassay on a Phantom Perfluorinated Plastic -- Characterization of Bacilli Spores by Surface-Enhanced Raman Spectroscopy, a Fast and Reliable Technique -- Development of a Novel Snom Probe for in Liquid Biological Samples -- A Point-of-Care Device for Immunosuppressants Monitoring in Transplanted Patients -- Optical Detection of Surfactants by Means of Reflective Phantom Interface Method -- Development of an Optical Sensing Strategy Based on Gold Nanoparticles Formation Driven by Polyphenols -- Deposition and Characterization of Laccase Thin Films Obtained by Matrix Assisted Pulsed Laser Evaporation.-Optical Characterization of Heavy Metal-Binding Proteins Bioconjugation On Porous Silicon Devices.
Keywords: Signal processing; Image processing; Speech processing systems; Electronics; Microelectronics; Signal, Image and Speech Processing; Electronics and Microelectronics, Instrumentation